Differentiating pulmonary hypertension associated with protein kinase inhibitors. (11th May 2022) - Jacobs, Joshua A.; Jahangir, Eiman; Ryan, John J.
Abstract: Protein kinase inhibitors (PKIs) have been implicated in pulmonary vascular toxicities including risk factors for at least three of the five World Health Organization groups of pulmonary hypertension (PH). These toxicities include direct drug‐induced pulmonary arterial hypertension, an increase in cardiomyopathies, and an increase in interstitial lung disease. On‐ and off‐target toxicities are common within multitargeted PKIs leading to cardiopulmonary toxicities. This review highlights the incidence, possible mechanisms, and management strategies for each group of possible PKI‐induced PH. Future identification and clarification of protein kinase pathways for both mechanisms of toxicity and pathophysiology for PH could lead to improvements in patient care in oncology and pulmonary vascular diseases.